The Effect Of Knowledge About Breast Cancer On Clinical Breast Examination Behavior - Indah Sulistyowati; Lucky Restyanti Wahyu Utami (Universitas Karya Husada Semarang, 2023)
ABSTRACTThe government has made various efforts, including early detection of breast cancer in women aged 30-50 years using the Clinical Breast Examination method. The incidence of breast cancer in Indonesia is 8,625 cases and 82% of them are found to be at an advanced stage. This is due to the reluctance of women to carry out early examinations. The purpose of this study was to determine the effect of knowledge about breast cancer on clinical breast examination behavior in women of childbearing age. The type of research used is quantitative research with an analytic survey research method, namely a survey or research that tries to explore how and why health phenomena occur. The population in this study were Women of Reproductive Age with a total sample of 33 respondents. Data collection using a questionnaire. Analysis of the relationship between the two variables using the Chi-Square test. From the results of the study it was found that most of the respondents had good knowledge about breast cancer, namely as many as 21 people (63.6%) and most of the respondents did not carry out Clinical Breast Examination as many as 18 people (54.5%) with a pvalue = 0.155 > 0.05 . so that there is no influence between Knowledge of Breast Cancer and the Implementation of Clinical Breast Examination in the Ngijo Village, Gunung Pati District, Semarang City. There needs to be an effort to increase knowledge and willingness to carry out Clinical Breast Examination as one of the efforts for Early Detection of Breast Cancer. Keywords: breast cancer; clinical breast examination; early detection ABSTRAK Pemerintah telah melakukan berbagai upaya antara lain deteksi dini kanker payudara pada perempuan usia 30-50 tahun dengan menggunakan metode Pemeriksaan Payudara Klinis. Angka kejadian kanker payudara di Indonesia sebanyak 8.625 kasus dan ditemukan 82% diantaranya sudah berada pada stadium lanjut. Hal ini disebabkan keengganan perempuan untuk melakukan pemeriksaan dini. Tujuan penelitian ini untuk mengetahui pengaruh pengetahuan tentang kanker payudara terhadap perilaku pemeriksaan payudara klinis pada wanita usia subur. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan metode penelitian survei analitik yaitu survei atau penelitian yang mencoba menggali bagaimana dan mengapa fenomena kesehatan terjadi. Populasi dalam penelitian ini adalah Wanita Usia Subur (WUS) dengan jumlah sampel dalam penelitian ini sejumlah 33 responden. Pengumpulan data dengan menggunakan kuesioner. Analisis hubungan antara dua variabel menggunakan uji Chi-Square. Dari hasil penelitian didapatkan bahwa sebagian besar responden memiliki pengetahuan baik tentang kanker payudara yaitu sebanyak 21 orang (63,6%) dan sebagian besar responden tidak melakukan Pemeriksaan Payudara Klinis sebanyak 18 orang (54,5%) dengan pvalue = 0,155 > 0,05. sehingga tidak ada pengaruh antara Pengetahuan tentang Kanker Payudara dengan Pelaksanaan Pemeriksaan Payudara Klinis di Kelurahan Ngijo Kecamatan Gunung Pati Kota Semarang. Perlu adanya upaya peningkatan pengetahuan dan kemauan untuk melakukan Pemeriksaan Payudara Klinis sebagai salah satu upaya Deteksi Dini Kanker Payudara. Kata kunci: kanker payudara;pemeriksaan payudara klinis; deteksi dini